2016
DOI: 10.4172/neuropsychiatry.1000142
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of mindfulness-based intervention for people with schizophrenia: a systematic review

Abstract: Background: With its known benefits in other mental illnesses, there have been increasing

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
(109 reference statements)
2
1
0
1
Order By: Relevance
“…This means that mindfulness therapy increases hopefulness and enhance recovery from illness among people with schizophrenia. Our findings support the previous evidence that mindfulness has positive impacts on recovery (Ganguly, 2018;Hayes, Herman, Castle, & Harvey, 2017;Lam & Chien, 2016;Soundy et al, 2015;Yılmaz & Okanlı, 2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This means that mindfulness therapy increases hopefulness and enhance recovery from illness among people with schizophrenia. Our findings support the previous evidence that mindfulness has positive impacts on recovery (Ganguly, 2018;Hayes, Herman, Castle, & Harvey, 2017;Lam & Chien, 2016;Soundy et al, 2015;Yılmaz & Okanlı, 2017).…”
Section: Discussionsupporting
confidence: 91%
“…A study by Yılmaz and Okanlı (2017) found that mindfulness-based therapy increased the patients' functional recovery as well as cognitive insight. Mindfulness is also found to promote composure and contributes to mood regulation, which leads to improvement of recovery factors, such as hope and life purpose (Ganguly, 2018;Lam & Chien, 2016). This study confirmed that mindfulness-based therapy positively influences patients' treatments particularly among those who were diagnosed with schizophrenia.…”
Section: Discussionsupporting
confidence: 64%
“…Mindfulness-based interventions (MBIs) have shown potential benefits for the treatment of OCD and SZ [4146]. Nevertheless, more research is required to identify the therapeutic components of mindfulness skills across diverse populations [45]. Based on a previous study conducted on a general population exploring relations between dispositional mindfulness and SC [47], we propose that mindfulness skills (i.e., the awareness of internal and external experiences by broadening one’s perspective without automatically reacting) will also be related to the ability to perceive, interpret and generate responses to the intentions, dispositions, emotions and behaviours of others (i.e., the core social cognition domains) in a clinical condition, particularly in SZ and OCD.…”
Section: Introductionmentioning
confidence: 99%
“…De hecho, un número creciente de estudios que muestran que las habilidades de mindfulness están relacionadas con las habilidades de cognición social como la teoría de la mente, procesamiento de emociones y empatía (Tripathi, Kar, y Shukla, 2018;Thabane et al, 2013;Teasdale et al, 2002;Tan, Lo, y Macrae, 2014). Las IBM han demostrado beneficios potenciales para tratar el TOC y la EZ (Gasnier et al, 2017;Bluett et al, 2014;Selchen et al, 2018;Ta-bak, Horan, y Green, 2015;Lam, y Chien, 2016). Sin embargo, se requiere más investigación para identificar los componentes terapéuticos específicos de los efectos de mindfulness, así como las facetas de mindfulness implicadas en sus resultados.…”
Section: Introductionunclassified